2024
DOI: 10.1021/acs.jafc.3c08239
|View full text |Cite
|
Sign up to set email alerts
|

High-Yield Synthesis of Lacto-N-Neotetraose from Glycerol and Glucose in Engineered Escherichia coli

Yingxue Liao,
Caiwen Lao,
Jinyong Wu
et al.

Abstract: Lacto-N-neotetraose (LNnT) is a neutral human milk oligosaccharide with important biological functions. However, the low LNnT productivity and the incomplete conversion of the intermediate lacto-N-tetraose II (LNT II) currently limited the sustainable biosynthesis of LNnT. First, the LNnT biosynthetic module was integrated in Escherichia coli. Next, the LNnT export system was optimized to alleviate the inhibition of intracellular LNnT synthesis. Furthermore, by utilizing rate-limiting enzyme diagnosis, the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Recently, Liao constructed a plasmid-free engineered E. coli to produce LNnT with a titer of 112.47 g/L by fed-batch cultivation . But the previously reported plasmid-dependent strains only produced LNnT with titers of approximately 20 g/L. , Thus, genomic integration for plasmid-free strains may be another research direction for LNDFH II biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Liao constructed a plasmid-free engineered E. coli to produce LNnT with a titer of 112.47 g/L by fed-batch cultivation . But the previously reported plasmid-dependent strains only produced LNnT with titers of approximately 20 g/L. , Thus, genomic integration for plasmid-free strains may be another research direction for LNDFH II biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Biosynthesis of HMOs in microbial strains has increasingly focused on optimizing fermentation conditions during large-scale production. For example, Liao et al performed a glucose/glycerol cofermentation strategy for lacto- N -neotetraose (LNnT) production; the carbon-source ratio (glucose/glycerol) in the supplement was optimized, and the highest titer of LNnT (94.08 g/L) was obtained when the ratio was 4:6 . To decrease the accumulation of the byproduct acetic acid in fed-batch fermentation.…”
Section: Resultsmentioning
confidence: 99%
“…At present, the microbial synthesis of 3–6 HMOs has become a mainstream approach. In contrast to 2′-FL and 3-FL, which have been extensively studied for efficient synthesis through the continuous development of microbial cell factories for over 10 years, very few studies have reported the microbial synthesis of DFL. Typically, to synthesize DFL, the initial step involves monofucosylation of lactose by an α-1,2-fucosyltransferase or α-1,3-fucosyltransferase.…”
Section: Introductionmentioning
confidence: 99%